John W. Colbert papers - Colbert, John W. (John William), 1880-1965.
Correspondence, diaries, speeches, lectures, articles, research materials, artwork, and other papers pertaining to Colbert's experiences researching tropical diseases primarily in Panama and Puerto Rico in the early 1900s, training nurses in Puerto Rico (1904-1905), assisting in relief efforts following the earthquake and firestorm in San Francisco (1906), providing medical care for the French and American armies in Belgium, the Gallipoli Peninsula (Turkey), and France during World War I, accompanying American Expeditionary Forces to Russia (1918), working as a physician in Tientsin, China (1920-1937), heading the first international relief expedition to reach Yokohama-shi (Japan) following the earthquake and fire in 1923, supporting women's participation in war efforts as the founder and head of the Woman's Ambulance and Defense Corps of America in the 1940s, serving as a U.S. Army officer in the South Pacific and Alaska during World War II, and pioneering modern medical techniques in Afghanistan following the war. Includes his observations of American and European nationals in Tientsin and on political and social disorder in China in the interwar period.
Library of Congress Prints and Photographs Division.
Pathologist and physician.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: France. -- Armée -- Medical personnel; United States. -- Army -- Medical personnel; United States. -- Army -- Officers; United States. -- Army. -- American Expeditionary Forces; San Francisco Earthquake and Fire, Calif., 1906.; Earthquakes -- Japan -- Yokohama-shi.; Fires -- California -- San Francisco; Fires -- Japan -- Yokohama-shi.; Medical care -- Afghanistan; Nursing -- Study and teaching -- Puerto Rico; Tropical medicine -- Panama; Tropical medicine -- Puerto Rico; Physicians, Foreign -- China; World War, 1914-1918 -- Medical care -- Belgium; World War, 1914-1918 -- Medical care -- France; World War, 1914-1918 -- Medical care -- Turkey; World War, 1939-1945 -- Alaska; World War, 1939-1945 -- South Pacific; World War, 1939-1945 -- Participation, Female; World War, 1939-1945 -- Women; China -- Politics and government -- 1912-1949.; China -- Social conditions; Gallipoli Peninsula (Turkey) -- History; Soviet Union -- History -- Allied intervention, 1918-1920.; Tianjin (China) -- History; Woman's Ambulance and Defense Corps of America; Pathologists; Physicians